2014
DOI: 10.1167/iovs.14-14391
|View full text |Cite
|
Sign up to set email alerts
|

Higher-Order Aberrations of Anterior and Posterior Corneal Surfaces in Patients With Keratectasia After LASIK

Abstract: Although flap creation and laser ablation were supposed to center on the primary line of sight in LASIK, keratectasia after LASIK showed coma-dominant HOAs at both corneal surfaces. This suggests that the cornea in keratectasia has optical properties similar to those in keratoconus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
2
7
0
1
Order By: Relevance
“…However, HOAs of the posterior corneal surface remained relatively stable. These results are consistent with those of other studies, which indicated that posterior corneal HOAs could complement corneal topography information, provide insight into the corneal biomechanical response, and provide valuable information that could be used to determine the cause of poor vision quality after corneal refractive surgery [ 2 , 3 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, HOAs of the posterior corneal surface remained relatively stable. These results are consistent with those of other studies, which indicated that posterior corneal HOAs could complement corneal topography information, provide insight into the corneal biomechanical response, and provide valuable information that could be used to determine the cause of poor vision quality after corneal refractive surgery [ 2 , 3 ].…”
Section: Discussionsupporting
confidence: 91%
“…Measurements of changes in wavefront aberrations are used to evaluate the impact of refractive surgery on vision quality [ 1 ]. Previous studies indicated that posterior corneal HOAs influenced corneal biomechanical responses and provided valuable information in determining the cause of poor vision quality after corneal refractive surgery [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced visual performance is secondary to refractive changes and increased high-order aberrations, particularly vertical coma. 74 Ectatic corneas usually present a myopic shift, because of central corneal protrusion, with increased astigmatism that might become irregular as the corneal bulge increases. 72 This leads to reduced best-spectacle corrected visual acuity that highly correlates with the degree of ablated tissue.…”
Section: Regeneration-related Complications: Visual Outcomes and Manamentioning
confidence: 99%
“…B. der späten Keratektasie. Das Auftreten der Letztgenannten wurde im Falle der Femto-LASIK bereits in der Literatur beschrieben [9][10][11][12]. Ein in diesem Zusammenhang wichtiger Parameter ist der Wert des sog.…”
Section: Impact Of Different Percent Tissue Altered Values On Visual unclassified